Enterprise Risk Management : Modern Approaches to Balancing Risk and Reward - Stefan Hunziker (Springer, 2023)
This textbook demonstrates how Enterprise Risk Management creates value in strategic- and decision-making-processes. The author introduces modern approaches to balancing risk and reward based on many examples of medium-sized and large companies from different industries. Since traditional risk management in practice is often an independent stand-alone process with no impact on decision-making processes, it is unable to create value and ties up resources in the company unnecessarily. Herewith, he serves students as well as practitioners with modern approaches that promote a connection between ERM and corporate management. The author demonstrates in a didactically appropriate manner how companies can use ERM in a concrete way to achieve better risk-reward decisions under uncertainty. Furthermore, theoretical and psychological findings relevant to entrepreneurial decision-making situations are incorporated.